Are Official Statistics Underexploited by Researchers and Policymakers? The Case of Agriculture Sector in Indonesia - Priyarsono, Dominicus Savio; Ahmad, Fahmi Salam (Agro Ekonomi, 2025)
This study is intended to evaluate the utilization of official statistics for academic research as well as for policymaking in agriculture sector in Indonesia.  To achieve the goal a conceptual framework of the relationship among official statistics, academic research, and policymaking was constructed.  The intensity of official statistics use for academic research was examined by analyzing the content of 7814 articles published in all 47 scientific journals officially affiliated with the Indonesian Society of Agricultural Economics (PERHEPI), 1978-2023.  It is found that the majority of the articles (62.6%) did not use BPS data. Furthermore, in the last two decades the utilization of secondary data for academic research papers tends to decrease, from 55.7% of the total articles published in 2004-2013 to 42.4% in 2014-2023. These results of calculation and other quantitative analyses were shown to 80 prominent resource persons for evaluation.  The majority of the respondents assessed that the level of utilization of BPS data was low or very low.  The factors that determine the level of utilization are relevance, accessibility, preference, and quality of the data.  The respondents also identified the needs to solve the problems of communication, collaboration, and coordination among the stakeholders of the ecosystem (official statistics agency, academia, and policymakers) to improve the functioning of the ecosystem of data utilization.  These findings are potentially beneficial for providing points of consideration in public discourses including those for revising the statistics law (UU Statistik) that has been undertaken by lawmakers in the Indonesian parliament (DPR) since 2023.